Do-It-Yourself integration of a paper sensor in a smart lid for medication adherence. (9th April 2019) - Khan, Sherjeel M; Qaiser, Nadeem; Shaikh, Sohail F; Ding, Lijie J; Hussain, Muhammad M
Abstract: Poor adherence to prescription medications causes approximately 125 000 deaths per year while an epidemic of a prescription drug overdose has been on the rise, resulting in an alarming number of deaths, 47 055 in 2014 only in the USA. Efforts from governments to address this issue are technologically inadequate. Once a patient leaves the pharmacy with a prescription drug container, no one, besides the patient, has control over the safe use of drugs. Here, we show a Do-It-Yourself (DIY) integration strategy to monitor drug intake, using a low-cost paper sensor-based flexible electronic system integrated inside the cap of a drug container. This electronic system consists of flexible modular decal sensors connected to a central flexible decal electronic interface, using a DIY compatible integration technique using an anisotropic conductive tape. We find that our DIY integration strategy gives the flexibility to develop customized versions of the system, depending on the requirements for different applications, ranging from ambient sensors to monitor the environment inside the container to security sensors that can detect any kind of mishandling with the prescription container. The add-on system is easy to install or remove, enabling an easy implementation for practical use that will ultimately mitigate drug overuse.